Variations in the temperature-humidity index and dorsal fat thickness during the last trimester of gestation and early postpartum period affect fertility of Bos indicus cows in the tropics - Díaz, Ramiro (2018)
In order to measure the infuence of the temperature-humidity index (THI) and the variation of fat thickness on reproductive performance, ninety-two Bos indicus cows kept under grazing conditions were used in two farms in Veracruz (Mexico) and Puntarenas (Costa Rica). THI was calculated with the average environmental temperature and relative humidity. Measurements of fat thickness (FAT) were taken two weeks apart from the last trimester of gestation to approximately 80 days postpartum (dpp). Natural breeding was used in both farms. Time to conception was calculated based on the interval from days at risk to conception (DRC), which had to be at least 28 dpp. THI was between 65.4 ± 2.9 and 73.2 ± 1.5 in Veracruz and 75.4 ± 0.26 and 76.5 ± 0.55 in Puntarenas. Variations in THI were observed in Puntarenas whereas in Veracruz THI variations were more prominent. In Veracruz, loss of fat during the last trimester of gestation was on average 8.5%, whereas in the postpartum period it was 18.4% (P = 0.042). In Puntarenas, the variation in the last trimester of gestation was on average 18.7% and in the postpartum period was 10.5% (P = 0.012). Te relative change in FAT in Veracruz was 36.7%, and in Puntarenas it was 29.3%. Overall, 60% of the cows became pregnant. FAT decreased the interval of DRC (R2 =0.06; P=0.033) with a high relationship (R2 =0.76; P< 0.0001) between THI and time to conception, in both farms. In conclusion, THI levels infuence the reproductive performance in early postpartum period afecting DRC.